2022
DOI: 10.3389/fpls.2022.944539
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Fine Mapping of qRPR1-3 and qRPR3-1, Two Major QTLs for Rind Penetrometer Resistance in Maize

Abstract: Stalk strength is one of the most important traits in maize, which affects stalk lodging resistance and, consequently, maize harvestable yield. Rind penetrometer resistance (RPR) as an effective and reliable measurement for evaluating maize stalk strength is positively correlated with stalk lodging resistance. In this study, one F2 and three F2:3 populations derived from the cross of inbred lines 3705I (the low RPR line) and LH277 (the high RPR line) were constructed for mapping quantitative trait loci (QTL), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Quantitative trait locus (QTL) analysis provides information on molecular markers associated with speci c traits in chromosomal regions that can be applied for marker-assisted selection (MAS) breeding (Scheben et al 2018). Hundreds of QTLs for stalk-lodging-related traits, including plant height (PH) and ear height (EH), plant diameter (PD), internode length (IL), and rind penetrometer resistance (RPR), have been identi ed in maize (Flint-Garcia et al 2003;Fei et al 2022;Hou et al 2022; Ku et al 2015; Yang et al 2015). However, because of large con dence intervals (CI) for any given QTL, and differences in the positions of QTLs that have the same effect in different mapping populations and environments, QTL ne mapping and gene validation is di cult and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait locus (QTL) analysis provides information on molecular markers associated with speci c traits in chromosomal regions that can be applied for marker-assisted selection (MAS) breeding (Scheben et al 2018). Hundreds of QTLs for stalk-lodging-related traits, including plant height (PH) and ear height (EH), plant diameter (PD), internode length (IL), and rind penetrometer resistance (RPR), have been identi ed in maize (Flint-Garcia et al 2003;Fei et al 2022;Hou et al 2022; Ku et al 2015; Yang et al 2015). However, because of large con dence intervals (CI) for any given QTL, and differences in the positions of QTLs that have the same effect in different mapping populations and environments, QTL ne mapping and gene validation is di cult and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
“…QTL mapping studies have been carried out to identify QTLs associated with RPR using different QTL mapping methods in various bi‐parent populations to dissect the genetic architecture of RPR in maize (Flint‐Garcia, Jampatong, et al., 2003; Hou et al., 2022; Hu et al., 2012; Li et al., 2014; Liu et al., 2022; Liu, Hu, et al., 2020; Meng et al., 2016; Peiffer et al., 2013; Zhang et al., 2019, 2020; Zhang, Liu, et al., 2018). These studies mapped hundreds of single QTLs, as well as a few pairs of epistatic QTLs, that contribute to the genetic basis of RPR variation in these bi‐parent populations.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical strength of the stem is intimately related to lodging resistance since this serves as the main mechanical support tissue for the aboveground plant. Numerous studies have shown that rind penetrometer resistance (RPR) and stem breaking strength (SBS) are reliable indicators for evaluating stalk lodging resistance (Hu et al, 2012;Hu et al, 2013;Liu et al, 2020;Zhang et al, 2020;Hou et al, 2022). Genetic analysis of the RPR trait in maize showed that it is affected by several minor QTL loci, some of which perform regulatory roles during multiple growth periods (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic force analysis indicates that F max contributed the most to the mechanical strength of the stem (Hu et al, 2012;Hu et al, 2013). Several studies have revealed that some genetic loci in SBS and RPR shared the same flanking markers or overlapping confidence intervals with lignin or cellulose concentration-related loci, suggesting that these traits may be influenced by some common genetic factors (Hu et al, 2012;Hou et al, 2022;Shao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%